Forgotten lives: Trans older adults living with dementia at the intersection of cisgenderism, ableism/cogniticism and ageism. (January 2022) - Baril, Alexandre; Silverman, Marjorie
There is little research at the international level to help us understand the experiences and needs of trans people living with dementia, despite population aging and the growing numbers of trans people including the first cohort of trans older adults. There is a need to understand the widespread barriers, discrimination and mistreatment faced by trans people in the health and social service system, and the fears trans people express about aging and dementia. Anecdotal evidence from the scarce literature on the topic of LGBTQ populations and dementia suggest that cognitive changes can impact on gender identity. For example, trans older adults with dementia may forget they transitioned and reidentify with their sex/gender assigned at birth or may experience 'gender confusion.' This raises crucial questions, for example regarding practices related to pronouns, care to the body (shaving, hair, clothes, etc.), social gendered interactions, health care (continuing or not hormonal therapy) and so on. This article fills a gap in current literature by offering a first typology of responses offered by academics who analyzed the topic of dementia and gender identity, to trans older adults with dementia who may be experiencing 'gender confusion, ' namely: (1) a gender neutralization approach; (2) a transaffirmative stable approach; and (3) a trans-affirmative fluid approach. After providing critical reflections regarding each approach, we articulate the foundations of a fourth paradigm, rooted in an interdisciplinary dialogue regarding the interlocking systems of oppression faced by trans older adults with dementia, namely ageism, ableism/sanism, and cisgenderism.